The impact of selected macroeconomic variables and the global financial crisis on the Malaysian economy - Nurshafiqah Mahfudz (Tanjong Malim, 2023)
The impact of selected macroeconomic variables and the global financial crisis on the Malaysian economy by Nurshafiqah Mahfudz